2018
DOI: 10.1002/pmic.201800008
|View full text |Cite
|
Sign up to set email alerts
|

Protein Network Analysis and Functional Studies of Calcium Oxalate Crystal‐Induced Cytotoxicity in Renal Tubular Epithelial Cells

Abstract: Our previous expression study has reported a set of proteins with altered levels in renal tubular cells after exposure to calcium oxalate monohydrate (COM) crystals, which are the main composition of kidney stones. However, their functional significance remained largely unknown. In this study, protein network analysis revealed that the significantly altered proteins induced by COM crystals were involved mainly in three main functional networks, including i) cell proliferation and wound healing; ii) oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…On the other hand, the decreased level of intracellular ATP is associated with reduced risk of oxidative stress and cell/tissue injury . It was thus plausible that the decreased intracellular ATP level observed in our present study was one of the protective mechanisms of estrogen to prevent renal cells/tissue from CaOx‐induced oxidative stress and renal injury frequently observed in kidney stone disease …”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…On the other hand, the decreased level of intracellular ATP is associated with reduced risk of oxidative stress and cell/tissue injury . It was thus plausible that the decreased intracellular ATP level observed in our present study was one of the protective mechanisms of estrogen to prevent renal cells/tissue from CaOx‐induced oxidative stress and renal injury frequently observed in kidney stone disease …”
Section: Discussionsupporting
confidence: 48%
“…[49,50] It was thus plausible that the decreased intracellular ATP level observed in our present study was one of the protective mechanisms of estrogen to prevent renal cells/tissue from CaOx-induced oxidative stress and renal injury frequently observed in kidney stone disease. [51,52]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the indirect mechanisms involving inflammation and oxidative stress injury that we have discussed, ceftriaxone calcium crystals could also harm tubular cells by directly inducing tubular cell death. Crystals are known to be cytotoxic when they come in direct contact with the tubular epithelium [ 28 ]. For example, Thongboonkerd et al have demonstrated that CaOx monohydrate crystals (COM) tightly adhere to MDCK cells with subsequent detrimental effects on the cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between the two common hydrated forms of CaOx crystals, CaOx monohydrate (COM) is more prominent and more pathogenic than CaOx dihydrate (COD) in kidney stone disease (Semangoen et al, 2008a;Semangoen et al, 2008b;Thongboonkerd et al, 2008;Peerapen et al, 2018). By differences in adhesive capability, atomic lattice, binding kinetics and surface atomic pattern of these two hydrated forms, COM crystal adheres more tightly to renal epithelial cell surface and is then internalized into the cells and subsequently transferred to the renal interstitium (Chiangjong and Thongboonkerd, 2012;Kanlaya et al, 2013;Chaiyarit et al, 2016;Chiangjong and Thongboonkerd, 2016;.…”
Section: Emerging Role Of Exosome In Kidney Stone Diseasementioning
confidence: 99%